3, 3′‐Diindolylmethane ameliorates experimental hepatic fibrosis via inhibiting miR‐21 expression. (17th September 2013) - Zhang, Zhengping; Gao, Zhongfei; Hu, Wei; Yin, Shan; Wang, Chunming; Zang, Yuhui; Chen, Jiangning; Zhang, Junfeng; Dong, Lei
Abstract : Background and Purpose: Hepatic fibrosis is a type of liver disease characterized by excessive collagen deposition produced by activated hepatic stellate cells (HSCs), and no appropriate drug treatment is available clinically. The microRNA, miR‐21 exhibits an important role in the pathogenesis and progression of hepatic fibrosis. 3, 3′‐Diindolylmethane (DIM) is a natural autolytic product in plants and can down‐regulate miR‐21 expression. Here we have assessed the therapeutic effects of DIM against hepatic fibrosis and investigated the underlying mechanisms. Experimental Approach: The effects of DIM on HSC activation were measured by analysing the expression of α‐smooth muscle actin and collagen I in both HSC‐T6 cell line and primary HSCs. Expression of miR‐21 was also measured after DIM treatment and the therapeutic effect of DIM was further studied in vivo, using the model of hepatic fibrosis induced by thioacetamide in mice. The antagonist oligonucleotide, antagomir‐21, was also used to suppress the effects of miR‐21. Key Results: DIM suppressed the central TGF‐β signalling pathway underlying HSC activation by down‐regulating the expression of miR‐21. The decreased miR‐21 expression was achieved by inhibiting the activity of the transcription factor, AP‐1. Moreover, DIM blunted the activation phenotype of primary HSCs. Administration of DIM in vivo attenuated liver fibrosis induced by thioacetamide, as assessed by collagen deposition and profiles of profibrogenic markers. Conclusions and Implications: DIM shows potential as a therapeutic agent for the treatment of hepatic fibrosis.